Understanding the Dynamic Linkages: Inflation, Real Balances, and Their Impact on Economic Growth in ECOWAS - Muhammad, Mansur; Baita, Abubakar Jamilu; Ansari, Saba (Department of Development Economics, Universitas Sriwijaya, 2024)
This study examines the dynamic relationship between growth, inflation, and real money balances in the Economic Community of West African States (ECOWAS). We apply a new approach by extending comprehensive econometric methods so that monetary dynamics can be better understood in the West African sub-region. The study obtained data from the World Bank from 2006 to 2021 and covered 15 countries. For robustness checks, we estimate dynamic ordinary least squares and fully modified ordinary least squares. These findings reveal the existence of a significant cointegration relationship between growth, real balance, and inflation. Furthermore, this study found that real balance has a positive long-run dynamic impact on growth. Likewise, there is a short-run positive impact of money and inflation on growth. We contribute to the literature on the money-growth nexus by focusing on West Africa, which faces macroeconomic vulnerabilities due to structural imbalances. These findings have policy implications for central banks and the Fiscal Agency. Central Banks must collaborate to reduce money in the informal sector, while Fiscal Authorities must control inflation collectively.